Lattice Dislocations Enhancing Thermoelectric PbTe in Addition to Band Convergence. Issue 23 (11th April 2017) - Chen, Zhiwei; Jian, Zhengzhong; Li, Wen; Chang, Yunjie; Ge, Binghui; Hanus, Riley; Yang, Jiong; Chen, Yue; Huang, Mingxin; Snyder, Gerald Jeffrey; Pei, Yanzhong
Abstract : Phonon scattering by nanostructures and point defects has become the primary strategy for minimizing the lattice thermal conductivity (κL ) in thermoelectric materials. However, these scatterers are only effective at the extremes of the phonon spectrum. Recently, it has been demonstrated that dislocations are effective at scattering the remaining mid‐frequency phonons as well. In this work, by varying the concentration of Na in Pb0.97 Eu0.03 Te, it has been determined that the dominant microstructural features are point defects, lattice dislocations, and nanostructure interfaces. This study reveals that dense lattice dislocations (≈4 × 10 12 cm −2 ) are particularly effective at reducing κL . When the dislocation concentration is maximized, one of the lowest κL values reported for PbTe is achieved. Furthermore, due to the band convergence of the alloyed 3% mol. EuTe the electronic performance is enhanced, and a high thermoelectric figure of merit, zT, of ≈2.2 is achieved. This work not only demonstrates the effectiveness of dense lattice dislocations as a means of lowering κL, but also the importance of engineering both thermal and electronic transport simultaneously when designing high‐performance thermoelectrics. Abstract : Eu‐doping effectively converges the valence bands of PbTe, while Na‐doping enables dense lattice dislocations, leading to an extremely low lattice thermal conductivity (κL ) of <0.4 W m −1 K −1 . This contributes to a high zT of ≈2.2, opening new possibilities for advancing thermoelectrics through dislocation and band‐engineering approaches.